Putative risk alleles for LATE‐NC with hippocampal sclerosis in population‐representative autopsy cohorts. (27th August 2019) - Hokkanen, Suvi R. K.; Kero, Mia; Kaivola, Karri; Hunter, Sally; Keage, Hannah A. D.; Kiviharju, Anna; Raunio, Anna; Tienari, Pentti J.; Paetau, Anders; Matthews, Fiona E.; Fleming, Jane; Graff, Caroline; et al.
Abstract: Limbic‐predominant age‐related TAR‐DNA‐binding protein‐43 (TDP‐43) encephalopathy with hippocampal sclerosis pathology (LATE‐NC + HS) is a neurodegenerative disorder characterized by severe hippocampal CA1 neuron loss and TDP‐43‐pathology, leading to cognitive dysfunction and dementia. Polymorphisms in GRN, TMEM106B and ABCC9 are proposed as LATE‐NC + HS risk factors in brain bank collections. To replicate these results in independent population‐representative cohorts, hippocampal sections from brains donated to three such studies (Cambridge City over 75‐Cohort [CC75C], Cognitive Function and Ageing Study [CFAS], and Vantaa 85+ Study) were stained with hematoxylin–eosin (n = 744) and anti‐pTDP‐43 (n = 713), and evaluated for LATE‐NC + HS and TDP‐43 pathology. Single nucleotide polymorphism genotypes in GRN rs5848, TMEM106B rs1990622 and ABCC9 rs704178 were determined. LATE‐NC + HS (n = 58) was significantly associated with the GRN rs5848 genotype (χ 2 (2) = 20.61, P < 0.001) and T‐allele (χ 2 (1) = 21.04, P < 0.001), and TMEM106B rs1990622 genotype (Fisher's exact test, P < 0.001) and A‐allele (χ 2 (1) = 25.75, P < 0.001). No differences in ABCC9 rs704178 genotype or allele frequency were found between LATE‐NC + HS and non‐LATE‐NC + HS neuropathology cases. Dentate gyrus TDP‐43 pathology associated with GRN and TMEM106B variations, but the association with TMEM106B nullified when LATE‐NC + HS cases were excluded. Our results indicate that GRN and TMEM106B are associated with severe loss of CA1 neurons in the aging brain, while ABCC9 was not confirmed as a genetic risk factor for LATE‐NC + HS. The association between TMEM106B and LATE‐NC + HS may be independent of dentate TDP‐43 pathology.